THE EROSION OF AL-MAWADDAH AND AR-RAHMAH VALUES IN MUSLIM MARRIAGES: A SOCIO-RELIGIOUS ANALYSIS OF MARITAL DYNAMICS IN LOMBOK - Asmuni; Yusdani; Januariansyah Arfaizar; Bin Sulong, Jasni (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Agama Islam Negeri Metro, 2025)
This study examines the dynamics of marital relationships within the Muslim community of Lombok, where high religiosity does not necessarily correspond to the achievement of the noble purposes of marriage. The high divorce rate is taken as evidence of difficulties in realizing the values of al-mawaddah (love) and ar-rahmah (compassion) within marital life. Employing a descriptive-analytic approach, the research integrates social exchange theory and a socio-religious framework, supported by empirical data on divorce rates. The findings indicate that the erosion of al-mawaddah and ar-rahmah values stems from a paradigm shift-from a marriage model grounded in mutual rights and obligations to one emphasizing individual freedom. This shift leads to emotional imbalance, communication breakdown, rising expectations and transformations in social values. From an Islamic perspective, marriage is not merely a transactional contract but a sacred covenant (mitsaqan ghalidzan) imbued with religious meaning. Al-mawaddah generates deep emotional attachment, while ar-rahmah nurtures endurance, patience, and sacrifice, thereby reinforcing marital harmony. The study contributes to understanding social changes within the marital institution in Lombok and underscores the significance of al-mawaddah and ar-rahmah as essential principles in sustaining marital stability and preventing divorce.